A machine learning evaluation of patient characteristics associated with prescribing of guideline-directed medical therapy for heart failure - Kim, Rachel; Suresh, Krithika; Rosenberg, Michael A.; Tan, Malinda S.; Malone, Daniel C.; Allen, Larry A.; Kao, David P.; Anderson, Heather D.; Tiwari, Premanand; Trinkley, Katy E. (Frontiers in Cardiovascular Medicine, 2023)
Introduction/Background Patients with heart failure and reduced ejection fraction (HFrEF) are consistently under-prescribed guideline-directed medications. Although many barriers to prescribing are known, identification of these barriers has relied on traditional a priori hypotheses or qualitative methods. Machine learning can overcome many limitations of traditional methods to capture complex relationships in data and lead to a more comprehensive understanding of the underpinnings driving under-prescribing. Here we used machine learning methods and routinely available electronic health record data to identify predictors of prescribing. Methods We evaluated the predictive performance of machine learning algorithms to predict prescription of 4 types of medications for adults with HFrEF: angiotensin converting enzyme inhibitor/angiotensin receptor blocker (ACE/ARB), angiotensin receptor-neprilysin inhibitor (ARNI), evidence-based beta blocker (BB), or mineralocorticoid receptor antagonist (MRA). The models with the best predictive performance were used to identify the top 20 characteristics associated with prescribing each medication type. Shapley values were used to provide insight into the importance and direction of the predictor relationships with medication prescribing. Results For 3,832 patients meeting inclusion criteria, 70% were prescribed an ACE/ARB, 8% an ARNI, 75% a BB and 40% an MRA. The best-predicting model for each medication type was a random forest (area under the curve: 0.788-0.821; Brier score: 0.063-0.185). Across all medications, top predictors of prescribing included prescription of other evidence-based medications and younger age. Unique to prescribing an ARNI, the top predictors included lack of diagnoses of chronic kidney disease, COPD, or hypotension, as well as being in a relationship, non-tobacco use, and alcohol use. Discussion/Conclusions We identified multiple predictors of prescribing for HFrEF medications that are being used to strategically design interventions to address barriers to prescribing and to inform further investigations. The machine learning approach used in this study to identify predictors of suboptimal prescribing can also be used by other health systems to identify and address locally relevant gaps and solutions to prescribing.